Factors related to age at natural menopause in China: results from the China Kadoorie Biobank. Issue 10 (2nd October 2021) - Wang, Meng; Kartsonaki, Christiana; Guo, Yu; Lv, Jun; Gan, Wei; Chen, Zheng-Ming; Li, Li-Ming; Hu, Chong-Gao; Yang, Ling; Yu, Min
Abstract : Supplemental Digital Content is available in the text Abstract: Objectives: The aim of this study was to investigate the potentially modifiable factors affecting age at natural menopause (ANM) in Chinese women. Methods: We used cross-sectional data from the China Kadoorie Biobank study which that recruited 0.5 million (0.3 million women) Chinese adults aged 30 to 79 from 2004 to 2008. Multinomial logistic regression models were used to examine the relationships between ANM and various factors recorded at baseline. Results: Among 87, 349 postmenopausal women, the mean ANM (SD) was 48.7 (4.3) years. Older age, being a housewife, earlier menarche, and passive smoking were associated with both premature menopause (PM, ie, ANM <40 years) and early menopause (EM, ie, ANM between 40 and 44 years). A higher odds for EM was observed in women who were widowed (odds ratio: 1.10, 95% confidence interval: 1.04-1.16), had spontaneous abortions (1.33 [1.05-1.69]), current regular smoking (1.19 [1.07-1.37]), and frequent spicy food intake (1.11 [1.05-1.08]). Higher socioeconomic status; later first birth; more live births and induced abortions; longer breastfeeding; tea drinking, as well as intakes of meat, fruits, dairy, and soybean products; and increased body mass index gain were inversely associated with PM and/or EM. In contrast, women who had more pregnancies, occasional alcohol drinking, higher levels of physical activity or body mass index, vitamin intake, and hypertension were more likely to have a later age at menopause (LM, ie, ANM ≥53 years). Conclusions: This large epidemiological study found a wide range of sociodemographic, lifestyle, dietary, and reproductive factors related to PM, EM, and LM in Chinese women.